The Relationship between Student Self-Efficacy and Students' Stress Level Undergoing Clinical Practice for the First Time - Vindo Galaresa, Achmad; Firmansyah, Firmansyah; Firdaus, Annisa Mazda; Reggi Prathama (Rifa'Institute, 2025)
Introduction: Stress is a common problem often experienced by nursing students during their clinical practice. Factors such as academic workload, new environments, and academic demands can increase the risk of stress. Self-efficacy are believed to play an important role in reducing stress levels. Objective: This study aims to determine the relationship between self-efficacy and first experience of clinical practice in students. Method: This study employs a descriptive correlational design with a cross-sectional approach, conducted at the Health Department of Subang State Polytechnic. The sample consisted of 120 students who would undergo clinical practice. Research instruments using questionnaire. Data analysis was conducted using the Spearman Rank test. Result and Discussion: The results showed that most students had high self-efficacy. There was a significant negative correlation between self-efficacy and stress levels (r = -0.310; p = 0.040). Programs focused on enhancing self-efficacy should be optimized within the nursing education context to better prepare students and enhance their ability to handle challenges in clinical practice settings. Conclusions: Self-efficacy were found to play a role in reducing students' stress levels.